The effect of solvent type on the extraction of soybean crude oil and its laboratory-scale cost analysis - Saputri, Desi Riana; Listyadevi, Yuniar Luthfia; Adiwibowo, Muhammad Triyogo; Alhanif, Misbahudin; Damayanti, Damayanti; Fahni, Yunita; Auriyani, Wika Atro; Sanjaya, Andri; Sufra, Rifqi; Yuniarti, Reni; Yusupandi, Fauzi; Syahriantoro, Nur Alfi; Kurniawansyah, Arief (Jurnal Teknika, 2023)
Soybeans (Glycine max) are a type of legume with moderately high fat content. Appropriate and safe types of solvents are essential in extracting fatty acids for consumption. This study aims to find an alternative solvent to replace n-hexane for extracting soybean oil and analyze its lab-scale production cost. Soybean oil was extracted by soxhlet extraction using ethanol, ethyl acetate, and n-hexane with a soybean-to-solvent ratio of 1:4 and 2:4 (w/v) and an extraction time of 1 and 2 hours. The results show that solvent polarity and soybean: solvent ratio affect the yield and density of the resulting extract. The greater the soybean-to-solvent ratio, the more oil is extracted until equilibrium. The highest yield was 36.25%, obtained at a material-to-solvent ratio of 2:4 (w/v) within 2 hours with ethyl acetate, and the oil density was 0.92 g/mL. The Gas Chromatography-Mass Spectrophotometry (GC-MS) analysis on the sample with the highest yield showed that the fatty acid composition was 34.36% linoleic acid, 22.12% palmitic acid, 19.40% stearic acid and 19.43% octadecadienoic acid. Ethyl acetate produces better yields and can be recommended as an alternative solvent to replace n-hexane for soybean oil extraction. The total extract production costs for 70% ethanol, 90% ethyl acetate, and 95% n-hexane solvents are IDR 780,847; 647,232; and 692,050, respectively.